Padrões de concentrações, mapeamento e estimativa de dose de radionuclídeos naturais em solos do Estado de Alagoas e distribuição da concentração de 137Cs - Filgueiras, Rogério de Andrade (2019)
This work provides useful information for geological and epidemiological studies in Brazil, through the knowledge of the concentration of radionuclides in soils. These works are scarce, mainly in the Northeast region, where may be areas of unknown radioactive anomalies. In addition, in the environmental area, the present work contributes to build a national database to be used, among other purposes, to evaluate changes in radionuclide concentrations in soils due to human activities. In other words, this study aimed at knowing the occurrence of radionuclides 40K, 226Ra, 228Ra and 137Cs in soils in the State of Alagoas. Concentration ranged from (6 ± 1) Bq kg-1 to (2160 ± 81) Bq kg-1 for 40K (average of 630 ± 25 Bq kg-1 ), from (5.0 ± 0.4) Bq kg-1 to (63 ± 2) Bq kg1 for 226Ra (average of 28 ± 1 Bq kg-1 ) and from (9.5 ± 0.5) Bq kg-1 to (157 ± 5) Bq kg-1 for 228Ra (average of 54 ± 2 Bq kg-1 ). While the average concentration for 226Ra agrees with the worldwide average, the average values found for 228Ra and 40K are above the worldwide average. The 40K measurements in the Alagoas backlands show a high concentration of this radionuclide. Concentrations of 137Cs ranged from (0.30 ± 0.08) Bq kg-1 to (1,13 ± 0,46) Bq kg-1 , values consistent with the literature.